Analysis of physical properties and bioavailability of encapulated forms of model essential fatty acids - A. V. Evteev; A. A. Krepneva; N. V. Gorbunova; L. S. Razumova; A. V. Bannikova (Новые технологии, 2017)
Physical properties and bioavailability of the encapsulated forms of essential fatty acids under the conditions of enzymatic hydrolysis simulating the human gastrointestinal tract have been analyzed. A direct link between mechanical characteristics of the capsules and transportation of bioactive substances within the experimental time has been established.